ANALISIS PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA AKUNTAN PUBLIK DI JAWA TENGAH (Students' Journal of Accounting and Banking, 2012)
The purpose of this study is to examine the influence of social factors, the suitability of the tasks, long-term consequences, affect, complexity, facilitated conditions. The population in this study was the auditors of Public Accountant Firms in Central Java. These samples of the study were determined by using random sampling method with the criteria that auditors have minimum 2-year experience. Data in this study were obtained by distributing questionnaires to respondents of 10 Public Accountant Firms in Semarang and Solo. While the hypothesis testing using a multiple regression analysis.Results of this study proved that the complexity and facilitating conditions affected the performance of public accounting. So, the higher the attitude of the consequences and the facilitating conditions the higher the performance of the accountant job.Keywords: Information technology, performance of public accountant, social factors, tasks, long term consequences, affects, complexity, and facilitated condition.